Structural confirmation of sulconazole sulfoxide as the primary degradation product of sulconazole nitrate - Qun Xu; Ashraf Khan; Di Gao; Kristie M. Adams; Fatkhulla Tadjimukhamedov; Shane Tan; John T. Simpson (Elsevier, 2018)
Sulconazole has been reported to degrade into sulconazole sulfoxide via sulfur oxidation; however, structural characterization data was lacking and the potential formation of an N-oxide or sulfone could not be excluded. To clarify the degradation pathways and incorporate the impurity profile of sulconazole into the United States Pharmacopeia-National Formulary (USP-NF) monographs, a multifaceted approach was utilized to confirm the identity of the degradant. The approach combines stress testing of sulconazole nitrate, chemical synthesis of the degradant via a hydrogen peroxide-mediated oxidation reaction, semi-preparative HPLC purification, and structural elucidation by LC-MS/MS and NMR spectroscopy. Structural determination was primarily based on the comparison of spectroscopic data of sulconazole and the oxidative degradant. The mass spectrometric data have revealed a McLafferty-type rearrangement as the characteristic fragmentation pathway for alkyl sulfoxides with a β-hydrogen atom, and was used to distinguish the sulfoxide from N-oxide or sulfone derivatives. Moreover, the generated sulconazole sulfoxide was utilized as reference material for compendial procedure development and validation, which provides support for USP monograph modernization. Keywords: Sulconazole nitrate, Sulconazole sulfoxide, Forced degradation, Structural characterization, LC-MS/MS